Estudio de reutilización del plástico reciclado en agregados para la elaboración de bloques, aplicados en la construcción de viviendas - Cedeño Mendoza, Johnny Omar (2024)
The study of reuse of recycled plastic in aggregates for the production of blocks, applied in the construction of homes, is a research topic that addresses the possibility of using recycled plastic as part of construction materials. This approach seeks to contribute to the reduction of plastic waste and promote more sustainable practices in the construction industry. The thesis investigates the plastic recycling process and its subsequent use as an aggregate in the manufacture of construction blocks. Technical, economic and environmental aspects of this technique are analyzed, as well as its feasibility and effectiveness in comparison with traditional materials.....